Histological description of the reproductive tract of male and female hatchlings of the magdalena river turtle (podocnemis lewyana). (2014)
In this study we review the macro and microscopic description of the reproductive system of male and female Podocnemis lewyana neonates of 3.5 months of age. We found macroscopic differences in the morphology of the gonads, with ovaries being twice longer that testes, and testes being twice wider than ovaries. Microscopically we identified several immature elements, such as the lack of muscle layer in the oviduct of reptile females, and simple epithelia instead of pseudostratified epithelia in the oviduct and epididymis described in adults. We also describe a black pigment observed macroscopically in the mesovarium and macroscopically and histologically in the epididymis. This pigment is compatible with the center of melano-macrophages described in other vertebrates. Finally we described a supporting mesenchymal structure, the appendage of the oviduct, with was much longer than what has been described in other Podocnemis species.